Preparation of Electrochemical Sensors Based on Graphene/Ionic Liquids and the Quantitative Detection and Toxicity Evaluation of Tetracycline - Meidan Lai; Linzhe Huang; Chengzhi Wang; Rui Zuo; Jun Liu (Nanomaterials)
Tetracycline antibiotics, which are recognized as emerging environmental pollutants, are overused and retained in large quantities in terminal water bodies, seriously endangering the ecological environment and human health. Therefore, establishing a straightforward, rapid, and sensitive method for quantitatively detecting and evaluating the toxicity of tetracyclines is highly important. Compared with traditional detection methods, emerging electrochemical methods have many advantages, such as simplicity and rapidity. In this work, an electrochemical sensor—a graphene ionic liquid composite glass carbon electrode (Gr/IL/GCE) with excellent catalytic properties for both tetracycline and cellular purine bases—was prepared by modifying a glassy carbon electrode with graphene and an ionic liquid for the quantitative detection of tetracycline and evaluation of its toxicity to cells. Graphene and the ionic liquid were uniformly distributed on the surface of the electrode and increased the electrically active surface area. The linear range of detection of tetracycline by a Gr/IL/GCE was 10–500 μM, with a detection limit of up to 2.06 μM. The Gr/IL/GCE demonstrated remarkable electrocatalytic efficacy against purine bases within human hepatocellular carcinomas (HepG2) cells. To evaluate the cytotoxicity of tetracycline, the median inhibition concentration (IC50) was determined, which was 243.82 μM.